Global research trends and hotspots in calcaneal fracture: A bibliometric analysis (2000–2021) - Cai, Yang-Ting; Song, Yu-Ke; He, Min-Cong; He, Xiao-Ming; Wei, Qiu-Shi; He, Wei (Frontiers in Surgery, 2023)
Background:Calcaneal fracture is common and carries high morbidity and disability.Thus, it has become a vital concern.Many topics concerning calcaneal fractures still remain controversial, and the global research trend has not been well-studied yet incalcaneal fracture field. We aim to analyse illustrate the development trends, overall knowledge structure and hotspots and frontiers in calcaneal fractures. Methods:Literature relating to calcaneal fractures from 2000 to 2021was retrieved from the database of Science Citation Index Expanded (SCIE) of Web of Science . Three bibliometric tools (Bibliometrix, CiteSpace, VOSviewer software)were used to conduct visualization and knowledge maps. Annual trends of publications, contributions of countries/regions, institutions, authors and journals, clustering of keywords ,hot topics, and frontiers were analyzed. Results: A total of 1,687 publications were included. The annual number of calcaneal fractures publications was the highest in 2019 worldwide. The United States has made the greatest contribution, with the largest number of publications and the highest H-index. Foot & Ankle International(167)was the most productive journals. The most prolific institutions were Hebei Medical University and University of California–San Francisco. Professors Schepers T, Rammelt S, Zwipp H, and Zhang YZ have made great achievements in this field. However, the collaboration between international institutions or researchers was relatively low and mainly conducted in European and American countries. All the keywords could be divided into 3 clusters:internal-fixation study of calcaneal fractures, fractures study and osteoporosis study of calcaneal fractures.A trend of balanced and diversified development existed in these clusters. Keywords with the ongoing bursts, including sinus tarsi approach, wound complications,minimally invasive technique, extensile lateral approach , surgical treatment and plate may continue to be the research hotspots in the near future. Conclusions: There will be an increasing number of publications on the calcaneal fractures research based on the current global trends, and the USA stays ahead in this field.International collaboration needs to be further strengthened. This study reveals the current research status and hot spots in the field of calcaneal fractures , which may help researchers to identify further potential perspectives on collaborators,research frontiers, and hot topics.